Intestinal Transcriptomic and Histologic Profiling Reveals Tissue Repair Mechanisms Underlying Resistance to the Parasite Ceratonova shasta - Damien E. Barrett; Itziar Estensoro; Ariadna Sitjà-Bobadilla; Jerri L. Bartholomew (Pathogens, 2021)
Background: Myxozoan parasites infect fish worldwide causing significant disease or death in many economically important fish species, including rainbow trout and steelhead trout (Oncorhynchus mykiss). The myxozoan Ceratonova shasta is a parasite of salmon and trout that causes ceratomyxosis, a disease characterized by severe inflammation in the intestine resulting in hemorrhaging and necrosis. Populations of O. mykiss that are genetically fixed for resistance or susceptibility to ceratomyxosis exist naturally, offering a tractable system for studying the immune response to myxozoans. The aim of this study was to understand how steelhead trout that are resistant to the disease respond to C. shasta once it has become established in the intestine and identify potential mechanisms of resistance. Results: Sequencing of intestinal mRNA from resistant steelhead trout with severe C. shasta infections identified 417 genes differentially expressed during the initial stage of the infection compared to uninfected control fish. A strong induction of interferon-gamma and interferon-stimulated genes was evident, along with genes involved in cell adhesion and migration. A total of 11,984 genes were differentially expressed during the late stage of the infection, most notably interferon-gamma, interleukin-6, and immunoglobulin transcripts. A distinct hardening of the intestinal tissue and a strong inflammatory reaction in the intestinal submucosa including severe hyperplasia and inflammatory cell infiltrates were observed in response to the infection. The massive upregulation of caspase-14 early in the infection, a protein involved in keratinocyte differentiation might reflect the rapid onset of epithelial repair mechanisms, and the collagenous stratum compactum seemed to limit the spread of C. shasta within the intestinal layers. These observations could explain the ability of resistant fish to eventually recover from the infection. Conclusions: Our results suggest that resistance to ceratomyxosis involves both a rapid induction of key immune factors and a tissue response that limits the spread of the parasite and the subsequent tissue damage. These results improve our understanding of the myxozoan–host dialogue and provide a framework for future studies investigating the infection dynamics of C. shasta and other myxozoans.